Felted cat caves - Breggin, Sarah (Independently Published, 2013)
Includes step by step instructions through felting a cat cave, including flowers, grass, flower buds, and advanced blocking. These cat caves are made directly from unspun, carded wool using the wet felting process. There is no yarn or knitting. This project is a large, multi-day project.